2022
DOI: 10.3390/molecules27061962
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Alleviates Astrocyte Activation and Oxidative Stress Induced by Hypoxia In Vitro

Abstract: Increasing evidence indicates that nobiletin (NOB) is a promising neuroprotective agent. Astrocyte activation plays a key role in neurodegenerative disorders. Thus, this study aims to investigate the effects of NOB on astrocyte activation and the potential mechanisms. In this study, astrocytes were exposed to hypoxia injury for 24 h to induce activation in vitro. Glial fibrillary acidic protein (GFAP) was chosen as a marker of astrocyte activation. To evaluate the effects of NOB on the migration of activated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Excessive ROS could lead to the disruption or depletion of antioxidant defense system and damage the function of antioxidant enzymes, such as SOD, simultaneously creating lipid peroxides, such as 4-HNE 31 . Nobiletin was previously reported to mitigate oxidative stresses in response to diverse stimuli 32 , 33 . In our study, the results of DCFH-DA staining showed that nobiletin considerably decreased the production of intracellular ROS triggered by cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive ROS could lead to the disruption or depletion of antioxidant defense system and damage the function of antioxidant enzymes, such as SOD, simultaneously creating lipid peroxides, such as 4-HNE 31 . Nobiletin was previously reported to mitigate oxidative stresses in response to diverse stimuli 32 , 33 . In our study, the results of DCFH-DA staining showed that nobiletin considerably decreased the production of intracellular ROS triggered by cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that NRF2 contributes to the regulation of antioxidant enzymes and plays cytoprotective roles to resist oxidative stresses 43 , while the transcriptional activation of NRF2 safeguarded auditory cells against cisplatin-elicited ototoxicity 44 , 45 . Numerous studies have shown that nobiletin activated NRF2 signaling pathway to resist oxidative stress triggered by hypoxia and nonalcoholic fatty liver diseases 32 , 33 . Furthermore, nobiletin has been demonstrated to directly augment the expression of NRF2 and HMOX1, even under physiological conditions in the absence of oxidative stress or mitochondrial dysfunction 46 .…”
Section: Discussionmentioning
confidence: 99%
“…These effects involve increasing levels of superoxide dismutase (SOD), catalase and GSH peroxidase [ 189 ]. Nobiletin, a polymethoxylated flavone derived from citrus peels, and resveratrol, a polyphenol present in grapes, promote HO-1 upregulation, an antioxidant which is associated with decline in ROS, reduction in astrocytic GFAP, and improved mitochondrial function [ 190 , 191 , 192 ]. Another study found that curcumin, a phenolic compound present in the Curcuma longa plant, might counteract some effects of oxidative stress such as mitochondrial dysfunction and astrogliosis [ 193 ].…”
Section: Astrocytes As a Therapeutic Target: Treatment And Neuroprote...mentioning
confidence: 99%
“…Nob was able to regulate oxidative stress and mitochondrial dysfunction to reduce liver inflammation and cell death [ 23 ]. Furthermore, Nob could alleviate hypoxia-induced oxidative stress, reduce ROS and malonaldehyde (MDA) production, and significantly improve mitochondrial dysfunction [ 24 ]. Increasing studies have shown that the protective effect of Nob on cells is achieved through the regulation of autophagy and the alleviation of inflammatory response.…”
Section: Introductionmentioning
confidence: 99%